PENERAPAN AKTIVITAS QUICK ON THE DRAW DALAM TATANAN PEMBELAJARAN KOOPERATIF UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIIc SMP NEGERI 5 RENGAT BARAT - Aztari, Annisa Rosa; ', Armis; Siregar, Syarifah Nur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research aims to improve the learning process and improve the student’s mathematic achievement through the implementation of activity quick on the draw in order cooperative learning cooperative. The research is the Classroom Action Research with two cycles. The research was conducted in class VIIc of 5 Junior High School Rengat Barat the odd semester of the 2016/2017 academic year with the subject of as many as 20 students. The research instrument are consists of learning devices and instrument data collectors. Learning device are consists of the Syllabus, Lesson plan, Student worksheet, and Card Question. The instrument data collector consists of the observation sheet and math test. Technique of data analysis is analysis of narrative descriptive and analysis of statistical descriptive. The result of the research show that the learning process has improved and the student’s mathematic achievement has improved after applying activity quick on the draw in order  cooperative learning. The percentage of students who achieve minimum mastery before the action is as much as 15% and at first cycle as much as 40% and at second cycle as much as 60%. Therefore, activity quick on the draw in order cooperative learning can be used as an alternative in learning. Keywords: Activity of Quick on The Draw, Cooperative Learning, Students Math Achievement, Clasroom Action Research